1996
DOI: 10.1056/nejm199610033351403
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis Associated with the Use of Alendronate

Abstract: Alendronate can cause chemical esophagitis, including severe ulcerations, in some patients. Recommendations to reduce the risk of esophagitis include swallowing alendronate with 180 to 240 ml (6 to 8 oz) of water on arising in the morning, remaining upright for at least 30 minutes after swallowing the tablet and until the first food of the day has been ingested, and discontinuing the drug promptly if esophageal symptoms develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
301
2
17

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 696 publications
(326 citation statements)
references
References 12 publications
6
301
2
17
Order By: Relevance
“…Gastrointestinal complaints were the main type of adverse event reported. Alendronate has been associated with potentially severe adverse esophageal effects 41,42 in approximately 1.3% of patients. 43 To decrease the likelihood of esophageal side effects, a formulation of 70 mg alendronate once weekly was selected for use.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal complaints were the main type of adverse event reported. Alendronate has been associated with potentially severe adverse esophageal effects 41,42 in approximately 1.3% of patients. 43 To decrease the likelihood of esophageal side effects, a formulation of 70 mg alendronate once weekly was selected for use.…”
Section: Discussionmentioning
confidence: 99%
“…The more notable adverse effects of bisphosphonates include hiatal hernias, dyspepsia, osteonecrosis of the jaw, and a newly defined class of characteristic low-energy subtrochanteric fractures. Gastrointestinal side effects are well documented in women, although they are also seen in men but at an unclear ratio regarding disease incidence in each sex [12]. Osteonecrosis of the jaw is an exceptional rare entity without sex specificity [41].…”
Section: Medication Response and Adherencementioning
confidence: 99%
“…There exists some evidence that branded Risedronate might be a slightly better suitable alternative bisphosphonate drug for gastrointestinal sensitive patients compared to original branded or generic Alendronate [7][8][9]32,33,[39][40][41][42][43][44][45][46]. Two recent studies have shown differences in tablets properties that might explain different rates of adverse events.…”
Section: Lower Bioavailability and Higher Rate Of Adverse Events Due mentioning
confidence: 99%